Telomere Length in Valve Tissue Is Shorter in Individuals With Aortic Stenosis and in Calcified Valve Areas - Saraieva, Ilona; Benetos, Athanase; Labat, Carlos; Franco-Cereceda, Anders; Bäck, Magnus; Toupance, Simon (Frontiers in Cell and Developmental Biology, 2021)
Background: Short telomere length (TL) is associated with age-related diseases, in particular cardiovascular diseases. However, whether the onset and course of aortic stenosis (AS) is linked to TL in aortic valves remains unknown. Objectives: To assess telomere dynamics (TL and telomerase activity) in aortic valves and the possible implication of TL in onset and course of AS. Methods: DNA was extracted from aortic valves obtained from 55 patients (78.2% men; age, 37-79 years), who had undergone replacement surgery due to AS (AS group, n=32), aortic valve regurgitation and aortic dilation (Non-AS group, n=23). TL was measured by telomere restriction fragment analysis (TRF) in calcified and non-calcified aortic valve areas. Telomerase activity was evaluated using telomerase repeat amplification protocol (TRAP) in protein extracts from non-calcified and calcified areas of valves obtained from 4 additional patients (50% men; age, 27-70 years). Results: TL was shorter in calcified aortic valve areas in comparison to non-calcified areas (n=31, 8.58±0.73 kb vs 8.12±0.75 kb, p<0.0001), whereas telomerase activity was not detected in any of those areas. Moreover, patients from AS group displayed shorter telomeres in non-calcified areas than those from the Non-AS group (8.40±0.64 kb vs 8.85±0.65, p=0.01). Conclusions: Short telomeres in aortic valves may participate in the development of AS, while concurrently the calcification process seems to promote further local decrease of TL in calcified areas of valves.